Next-generation sequencing identified SPATC1L as a possible candidate gene for both early-onset and age-related hearing loss. - Morgan, Anna; Vuckovic, Dragana; Krishnamoorthy, Navaneethakrishnan; Rubinato, Elisa; Ambrosetti, Umberto; Castorina, Pierangela; Franzè, Annamaria; Vozzi, Diego; La Bianca, Martina; Cappellani, Stefania; Di Stazio, Mariateresa; Gasparini, Paolo; et al. (Eur J Hum Genet, 2019)
Hereditary hearing loss (HHL) and age-related hearing loss (ARHL) are two major sensory diseases affecting millions of people worldwide. Despite many efforts, additional HHL-genes and ARHL genetic risk factors still need to be identified. To fill this gap a large genomic screening based on next-generation sequencing technologies was performed. Whole exome sequencing in a 3-generation Italian HHL family and targeted re-sequencing in 464 ARHL patients were performed. We detected three variants in SPATC1L: a nonsense allele in an HHL family and a frameshift insertion and a missense variation in two unrelated ARHL patients. In silico molecular modelling of all variants suggested a significant impact on the structural stability of the protein itself, likely leading to deleterious effects and resulting in truncated isoforms. After demonstrating Spatc1l expression in mice inner ear, in vitro functional experiments were performed confirming the results of the molecular modelling studies. Finally, a candidate-gene population-based statistical study in cohorts from Caucasus and Central Asia revealed a statistically significant association of SPATC1L with normal hearing function at low and medium hearing frequencies. Overall, the amount of different genetic data presented here (variants with early-onset and late-onset hearing loss in addition to genetic association with normal hearing function), together with relevant functional evidence, likely suggest a role of SPATC1L in hearing function and loss.

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Pharmacogenetics driving personalized medicine: analysis of genetic polymorphisms related to breast cancer medications in Italian isolated populations. - Cocca, Massimiliano; Bedognetti, Davide; La Bianca, Martina; Gasparini, Paolo; Girotto, Giorgia (J Transl Med, 2016)
BACKGROUND: Breast cancer is the most common cancer in women characterized by a high variable clinical outcome among individuals treated with equivalent regimens and novel targeted therapies. In this study, we performed a population based approach intersecting high-throughput genotype data from Friuli Venezia Giulia (FVG) isolated populations with publically available pharmacogenomics information to estimate the frequency of genotypes correlated with responsiveness to breast cancer treatment thus improving the clinical management of this disease in an efficient and cost effective way. METHODS: A list of 80 variants reported to be related to the efficacy or toxicity of breast cancer drugs was obtained from PharmGKB database. Fourty-one were present in FVG, 1000G European (EUR) and ExAC (Non Finnish European) databases. Their frequency was extracted using PLINK software and the differences tested by Fisher's exact test. RESULTS: Statistical analyses revealed that 13 out of the 41 (32 %) variants were significantly different in frequency in our sample as compared to the EUR/ExAC cohorts. For nine variants the available level of evidence (LOE) included polymorphisms related to cyclophosphamide, tamoxifen, doxorubicin, fluorpyrimidine and paclitaxel. In particular, for trastuzumab two variants were detected: (1) rs1801274-G within FCGR2A and associated with decreased efficacy (LOE 2B); (2) rs1136201-G located within ERBB2 and associated with increased toxicity (LOE 3). Both these two variants were underrepresented in the FVG population compared to EUR/ExAC population thus suggesting a high therapeutic index of this drug in our population. Moreover, as regards fluoropyrimidines, the frequency of two polymorphisms within the DPYD gene associated with drug toxicity (e.g., rs2297595-C allele and rs3918290-T allele, LOE 2A and 1, respectively) was extremely low in FVG population thus suggesting that a larger number of FVG patients could benefit from full dosage of fluoropyrimidine therapy. CONCLUSIONS: All these findings increase the overall knowledge on the prevalence of specific variants related with breast cancer treatment responsiveness in FVG population and highlight the importance of assessing gene polymorphisms related with cancer medications in isolated communities.

Understanding the role of personality and alexithymia in food preferences and PROP taste perception. - Robino, Antonietta; Mezzavilla, Massimo; Pirastu, Nicola; La Bianca, Martina; Gasparini, Paolo; Carlino, Davide; Tepper, Beverly J (Physiol Behav, 2016)
Taste perception and food preferences are influenced by a variety of factors, including personality characteristics. The aims of this study were to examine the role of personality characteristics, such as alexithymia (a personality construct characterized by inability to identify, describe, and work with one's own feelings), in: 1) taste responses to the bitter genetic taste-marker PROP and 2) food liking. We studied 649 healthy subjects residing in six genetically-isolated villages of Northeast Italy. Data on PROP taste responsiveness, food liking, personality characteristics and TAS2R28 genotypes were collected. Results showed that PROP non-tasters had higher alexithymia scores than PROP tasters. Moreover, the presence of alexithymia in heterozygous individuals for the rs1726886 polymorphism of the TAS2R38 gene was associated with a reduction in the perceived intensity of PROP. Finally, higher alexithymia scores were associated with liking of alcohol, sweets and fats/meats whereas lower alexithymia scores were related to liking of vegetables, condiments and strong cheeses, Measures of temperament, character, anxiety and depression were also related to food liking. Our findings suggest that: 1) alexithymia, in addition to the TAS2R38 polymorphism, may play a role in responsiveness to the aversive and bitter taste of PROP; and 2) alexithymia, in combination with other personality traits, may provide important insights for better understanding food liking.

The first trimester gravid serum regulates procalcitonin expression in human macrophages skewing their phenotype in vitro. - Rami, Damiano; La Bianca, Martina; Agostinis, Chiara; Zauli, Giorgio; Radillo, Oriano; Bulla, Roberta (Mediators Inflamm, 2014)
Procalcitonin (PCT) is one of the best diagnostic and prognostic markers in clinical practice, widely used to evaluate the evolution of bacterial infections. Although it is mainly produced by thyroid, during sepsis almost all the peripheral tissues are involved in PCT production. Parenchymal cells have been suggested as the main source of PCT expression; however the contribution of macrophages is not clear yet. In response to environmental cues, tissue macrophages acquire distinct functional phenotypes, ranging from proinflammatory (M1) to anti-inflammatory (M2) phenotype. Macrophages at the fetal-maternal interface show immunosuppressive M2-like activities required for the maintenance of immunological homeostasis during pregnancy. This study aims to clarify the ability to synthesise PCT of fully differentiated (M0), polarized (M1/M2) macrophages and those cultured either in the presence of first trimester gravid serum (GS) or pregnancy hormones. We found out that M1 macrophages upregulate PCT expression following LPS stimulation compared to M0 and M2. The GS downregulates PCT expression in macrophages, skewing them towards an M2-like phenotype. This effect seems only partially mediated by the hormonal milieu. Our findings strengthen the key role of macrophages in counteracting inflammatory stimuli during pregnancy, suggesting PCT as a possible new marker of M1-like macrophages.
Keywords: Biomarkers; Calcitonin; Cells, Cultured; Chorionic Gonadotropin; Estradiol; Female; Gene Expression Regulation; Homeostasis; Humans; Inflammation; Macrophages; Monocytes; Phenotype; Pregnancy; Pregnancy Trimester, First; Protein Precursors; Serum; Up-Regulation